Rotavirus VP6 Adjuvant Effect on Norovirus GII.4 Virus-Like Particle Uptake and Presentation by Bone Marrow-Derived Dendritic Cells In Vitro and In Vivo - Kirsi Tamminen; Suvi Heinimäki; Timo Vesikari; Vesna Blazevic (Journal of Immunology Research)
We have previously shown that rotavirus (RV) inner capsid protein VP6 has an adjuvant effect on norovirus (NoV) virus-like particle- (VLP-) induced immune responses and studied the adjuvant mechanism in immortalized cell lines used as antigen-presenting cells (APCs). Here, we investigated the uptake and presentation of RV VP6 and NoV GII.4 VLPs by primary bone marrow-derived dendritic cells (BMDCs). The adjuvant effect of VP6 on GII.4 VLP presentation and NoV-specific immune response induction by BMDC in vivo was also studied. Intracellular staining demonstrated that BMDCs internalized both antigens, but VP6 more efficiently than NoV VLPs. Both antigens were processed and presented to antigen-primed T cells, which responded by robust interferon γ secretion. When GII.4 VLPs and VP6 were mixed in the same pulsing reaction, a subpopulation of the cells had uptaken both antigens. Furthermore, VP6 copulsing increased GII.4 VLP uptake by 37% and activated BMDCs to secrete 2-5-fold increased levels of interleukin 6 and tumor necrosis factor α compared to VLP pulsing alone. When in vitro-pulsed BMDCs were transferred to syngeneic BALB/c mice, VP6 improved NoV-specific antibody responses. The results of this study support the earlier findings of VP6 adjuvant effect in vitro and in vivo.